Perceptions on tailored messages from a values clarification tool: a mixed-methods study of older adults with cancer - Cole, Amy C.; Kwong, Elizabeth; Mhina, Carl; King, Andy J.; Mazur, Lukasz; Richardson, Daniel R. (Frontiers in Communication, 2024)
Introduction The purpose of this study was to assess whether varying input communication factors impacted participants’ perceived confidence, motivation, and likelihood to act (i.e., share or discuss their preferences and values with their clinician or family/caregiver) when receiving tailored communication from a values-clarification tool. Methods This study was conducted over a two-month period at the North Carolina Basnight Cancer Hospital. Patients with hematologic malignancies participated in evaluating three distinct messages that varied on three input communication factors. Results Results from this study indicate that most study participants preferred messages that were moderately direct, contained succinct question prompts, and that were empowering. Results also indicate that diverse perspectives and external influences may impact confidence and motivation toward discussing preferences with their clinicians. Discussion Our findings suggest the importance of validating the input communication factors within values-clarification tools before presenting results to patients and the need to evaluate potential disparities in patients’ participation toward discussing their preferences. Evidence from this study provides direction for future research efforts focused on improving shared decision-making among older adults.